An essential role for the RNA helicase DDX6 in NMDA receptor-dependent gene silencing and dendritic spine shrinkage - Fathima M. Perooli; Kevin A. Wilkinson; Kate Pring; Jonathan G. Hanley (Scientific Reports, 2024)
Abstract MicroRNAs (miRNAs) repress translation of target mRNAs by associating with Argonaute (Ago) proteins in the RNA-induced silencing complex (RISC) to modulate protein expression. Specific miRNAs are required for NMDA receptor (NMDAR)-dependent synaptic plasticity by repressing the translation of proteins involved in dendritic spine morphogenesis. Rapid NMDAR-dependent silencing of Limk1 is essential for spine shrinkage and requires Ago2 phosphorylation at S387. Not all gene silencing events are modulated by S387 phosphorylation, and the mechanisms that govern the selection of specific mRNAs for silencing downstream of S387 phosphorylation are unknown. Here, we show that NMDAR-dependent S387 phosphorylation causes a rapid and transient increase in the association of Ago2 with Limk1, but not Apt1 mRNA. The specific increase in Limk1 mRNA binding to Ago2 requires recruitment of the helicase DDX6 to RISC. Furthermore, we show that DDX6 is required for NMDAR-dependent silencing of Limk1 via miR-134, but not Apt1 via miR-138, and is essential for NMDAR-dependent spine shrinkage. This work defines a novel mechanism for the rapid transduction of NMDAR stimulation into miRNA-mediated translational repression of specific genes to control dendritic spine morphology.